Non-alcoholic fatty liver disease and cardiovascular risk in type 2 diabetes mellitus: Analysis of case series from an academic center - BOUDAOUD, K; CHEBEL, I; NOURI, N (Journal of Human Sciences, 2022)
AIM= Cardiovascular risk assessment(CVR) in type 2 diabetic (MDT2) patients with Non-alcoholic fatty liver disease(NAFLD) Patients and methods Retrospective study of 89 T2DM with ultrasound hepatic steatosis. The CVR assessed according to the ESC 2021 guidelines. The risk of fibrosis is assessed by the NAFLD fibrosis score (NFS). Fibrosis was assessed using the fibrosis-4 score(Fib-4). Results. NAFLD found in 23% of patients without NASH, aged 52±8 years, diabetic for 13.55±7 years, sex ratio F:H 1.5. The CVR is very high in 80%, moderate in 20% of patients. We note 55% of obese patients, 70% of dyslipidemic patients and 20% of cases of hepatic cytolysis. NFS indicates fibrosis in 25% and remains indeterminate in 30% of cases. Discuss. NAFLD is often associated with insulin resistance and strongly associated with DMT2 and a higher risk of CVD. In addition to being at risk of advanced fibrosis and cirrhosis, NAFLD patients are also at higher risk of cardiovascular disease which is consistent with our results. Close monitoring of diabetics with NAFLD is recommended to prevent major vascular events. Risk stratification scores are needed that address both the risk for advanced liver disease and CVD.